Missionary Linguistics VI missionary linguistics in Asia : selected papers from the tenth International Conference on Missionary Linguistics, Rome, 21-24 March 2018 - Zwartjes, Otto; De Troia, Paolo (Amsterdam studies in the theory and history of linguistic science. Studies in the history of the language sciences ;, 2021)
"This is the sixth volume to be dedicated to the pioneering linguistic work produced by missionaries in Asia. This volume presents research into the documentation, study and description of Chinese, Japanese, Vietnamese and Tamil. It provides a selection of papers which primarily concentrate on the Society of Jesus and their linguistic production, but also covers linguistic works written by Franciscans, the Order of Discalced Carmelites and works of other religious institutions, such as the Propaganda Fide and the Missions Étrangères de Paris. New insights are provided regarding these works and their reception among European scholars interested in these 'exotic' languages and cultures. Each text is placed in its historical context and various approaches to some of the most important descriptive problems faced by these linguists avant la lettre are analyzed, such as the establishment of an adequate romanization system, the description of typological features of these Asian languages, such as tonality and aspiration in Chinese and Vietnamese, agglutination and derivational morphology in Japanese and Tamil, and, pragmatics, in particular politeness in Japanese. This volume not only looks at methodology and descriptive techniques, but also comments on missionary linguistic policies in Asia and offers articles of interest to historiographers of linguistics, historians, typologists, descriptive linguists and those interested in translation studies"--